Strategi Bidang Program LPP TVRI Pusat Dalam Meningkatkan Mutu Tayangan - Munanjar, Azwar; Wibowo, Enggar Cahyo (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2024)
This study aims to describe the management strategy of the Central TVRI LPP program in improving the quality of shows based on the organization’s Communication Theory in it. Furthermore, this study aims to determine the supporting and inhibiting factors of the airing of Central TVRI programs in improving the quality of impressions. The type research used is a qualitative approach. The data sources obtained from Central TVRI emppyees using data collection methods, namely observation, interview and documentation. The results showed that improving the quality of impressions, Central TVRI implemented varios management strategies. They are 1) Prepare program planning, 2) Produce or purchase programs, 3) Supervise and evaluate each program, 4) Supervise and evaluate each program. The supporting factors of the Central TVRI programs are the breadth of location, power and broadcast coverage so that it is easily accessible to all viewers throughout Indonesia. While the inhibiting factors are human resources that continue to decrease and the reduction of professional experts in their fields, as well as the limited state budget which has an impact on suboptimal production equipment. After conducting research at Central TVRI concluded, although TVRI’s audience is slight inferior to the number of other private television viewers, TVRI still conducts and makes programs by making broadcast strategies and updating its programs so that TVRI viewers, interest returns